A description of sleep behaviour in healthy late pregnancy, and the accuracy of self-reports. Issue 1 (December 2016) - McIntyre, Jordan; Ingham, Cayley; Hutchinson, B.; Thompson, John; McCowan, Lesley; Stone, Peter; Veale, Andrew; Cronin, Robin; Stewart, Alistair; Ellyett, Kevin; Mitchell, Edwin
Abstract Background The importance of maternal sleep and its contribution to maternal and fetal health during pregnancy is increasingly being recognised. However, the ability to accurately recall sleep practices during pregnancy has been questioned. The aim of this study is to test the accuracy of recall of normal sleep practices in late pregnancy. Methods Thirty healthy women between 35 and 38 weeks of gestation underwent level III respiratory polysomnography (PSG) with infrared digital video recordings in their own homes. Data regarding sleep positions, number of times getting out of bed during the night and respiratory measures were collected. A sleep questionnaire was administered the morning after the recorded sleep. Continuous data were assessed using Spearman's Rho and Bland-Altman. Cohen's Kappa was used to assess recall in the categorical variables. Results Two-thirds of participants went to sleep on their left side. There was good agreement in sleep onset position between video and questionnaire data (Kappa 0.52), however the there was poor agreement on position on wakening (Kappa 0.24). The number of times getting out of bed during the night was accurately recalled (Kappa 0.65). Twenty five out of 30 participants snored as recorded by PSG. Questionnaire data was inaccurate for this measure. Bland-Altman plots demonstrated acceptable agreement between video and questionnaire data for estimated sleep duration, but not the time taken to fall asleep (sleep latency). One participant had mild obstructive sleep apnoea and another probable high upper airways resistance. Conclusions Sleep onset position, sleep duration and the number of times getting out of bed during the night were accurately recalled, but sleep latency and sleep position on waking were not. This study identifies the sleep variables that can be accurately obtained by questionnaire and those that cannot.